Implementasi Metode Algoritma Certainty Factor Dalam Mendiagnosa Gejala Infeksi Bakteri Salmonella - Abdul Kadir Parewe, Andi Maulidinnawati; Ratnawati, Ratnawati; Indra, Muhammad (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2021)
The world of health is growing rapidly as well as many types of diseases that appear over time. Several levels of mutated disease are based on new symptoms found by researchers in their respective fields of expertise, one of which is salmonella bacterial infection. Most patients often do not recognize the symptoms of disease that often arise due to the bacterial infection so that it can aggravate the disease when bacteria have multiplied in the body. Therefore, with the implementation of the certainty factor algorithm method as a solution to diagnose the symptoms of salmonella bacterial infection and to make it easier for doctors to diagnose patients with the use of the system and time efficiency at work. The results of the application of the certainty factor algorithm method based on this study get a percentage of 80% and are included in the feasible category.